Are Serum Ion Levels Elevated in Pediatric Patients With Metal Implants?. Issue 3 (7th March 2022) - Mathew, Smitha E.; Xie, Yong; Bagheri, Leila; Claton, Liam E.; Chu, Lin; Badreldin, Amr; Abdel, Matthew P.; van Wijnen, Andre J.; Haft, Geoffrey F.; Milbrandt, Todd A.; Larson, A. Noelle
Abstract : Background: Previous studies report elevated serum titanium (Ti) levels in children with spinal implants. To provide additional data on this topic, we sought to assess serum ion levels at multiple timepoints in pediatric patients with growing spine devices, spinal fusion instrumentation, and extremity implants placed for fracture treatment. We hypothesized that serum Ti, cobalt (Co), and chromium (Cr) levels would be elevated in pediatric patients with growing spine devices compared with patients with extremity implants. Methods: Pediatric patients undergoing any primary spine implant placement, those with spine implant revision or removal surgery and patients with other appendicular implant removal had serum Ti, Co, and Cr ion levels drawn at the time of surgery. Fifty-one patients (12 growing spine devices, 13 fusions, and 26 extremity implants) had one set of labs, 31 of whom had labs drawn both preoperatively and postoperatively. Biopsies obtained from tissue specimens at the time of implant revision were analyzed histologically for the presence of metal debris and macrophage activity. Results: Patients with growing spine implants had elevated serum Ti (3.3 vs. 1.9 ng/mL, P =0.01) and Cr levels (1.2 vs. 0.27 ng/mL, P =0.01) in comparison to patients with fusion rods or extremity implants. With respect to patients with extremity implants, patients with growing spine devices had elevated serum Ti (3.3 vs. 0.98 ng/mL, P =0.013), Co (0.63 vs. 0.26 ng/mL, P =0.017), and Cr levels (1.18 vs. 0.26 ng/mL, P =0.005). On matched pairs analysis, patients who had labs drawn before and after spine implantation had significant increase in serum Ti levels (0.57 vs. 3.3 ng/mL, P =0.02). Histology of tissue biopsies adjacent to growing spine implants showed presence of metal debris and increased macrophage activity compared with patients with extremity implants. Conclusion: Serum Ti, Co, and Cr levels are elevated in children with spinal implants compared with those with extremity implants, particularly in those with growing spine devices. However, the clinical significance of these findings remains to be determined. Level of Evidence: Level II—prospective comparative study.